585 Intralesional injection of rose bengal improves the efficacy of gemcitabine chemotherapy against pancreatic cancer. (10th December 2020) - Innamarato, Patrick; Pilon-Thomas, Shari; Morse, Jennifer; Asby, Sarah; Mackay, Amy; Beatty, Matthew; Blauvelt, Jaime; Kidd, Scott; Mullinax, John
Abstract : Background: Chemotherapy regimens that include gemcitabine are considered standard of care in patients with advanced pancreatic ductal adenocarcinoma (PDAC). However, most patients with PDAC die within 2 years of diagnosis, even with these standard of care regimens. In this study, we explored the ability of intratumoral injections of PV-10, a 10% solution of rose bengal, to induce lesion-specific ablation and control of metastatic pancreatic tumors in a murine model. Methods: PV-10 was cultured with human pancreatic cancer cell lines overnight and cell death was measured via Annexin-V and DAPI staining. Murine pancreatic tumor cells (Panc02) were injected subcutaneously in one flank to establish a single tumor model; to establish a bilateral tumor model, Panc02 tumor cells were implanted in the opposite flanks. On day 7, a single tumor was treated with intralesional PV-10. Gemcitabine (60 mg/kg) was injected intraperitoneally twice per week for 2 weeks. These experiments were repeated using Panc02 cells modified to overexpress the neoantigen ovalbumin (OVA). Control mouse tumor were directly injected with PBS. Tumor growth of PV-10 injected tumors and non-injected bystander tumors on the opposite flank were measured. Damage associated molecular patterns (DAMPs) in serum and immune cell frequencies within the spleens of tumor-bearing mice were measured to identify an associated systemic response with tumor lytic treatment regimen. Results: We established that less than 50% of human and murine pancreatic cells were alive after a 24 hour incubation with 200µM PV-10 in vitro. The combination of intralesional PV-10 with the systemic administration of gemcitabine delayed the growth treated tumors and non-injected distal tumors. In contrast, gemcitabine monotherapy failed to delay tumor growth in bilateral Panc02 tumor models. We observed that this treatment strategy was markedly more successful in immunogenic Panc02OVA tumors resulting in lesion-specific ablation in 5/8 mice compared to 0/8 mice that were treated with gemcitabine monotherapy. This suggests that the combination therapy enhanced the immune-mediated clearance of tumors. Moreover, regression of tumors in mice that received PV-10 in combination with gemcitabine was associated with the depletion of splenic CD11b+Gr-1+ cells and increases in damage associated molecular patterns HMGB1, S100A8, and IL-1α. Conclusions: Together, these results demonstrate that intralesional therapy with PV-10 can enhance the efficacy gemcitabine against pancreatic tumors. Ethics Approval: Studies were performed under approved Institutional Review Board (IRB) laboratory protocols at the H. Lee Moffitt Cancer Center (Tampa, FL).